2019
DOI: 10.1371/journal.pone.0221566
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in corneal neovascularization in response to superficial corneal cautery in the rat

Abstract: Sex-based differences in susceptibility have been reported for a number of neovascular ocular diseases. We quantified corneal neovascularization, induced by superficial silver nitrate cautery, in male and female inbred albino Sprague-Dawley, inbred albino Fischer 344, outbred pigmented Hooded Wistar and inbred pigmented Dark Agouti rats of a range of ages. Corneal neovascular area was quantified on haematoxylin-stained corneal flatmounts by image analysis. Pro-and anti-angiogenic gene expression was measured e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…46 Also, recent studies provided evidence that male rats and humans are more prone to corneal neovascularization than females and that males had a higher level of pro-atherogenic molecules, including VEGF (vascular endothelial growth factor)-A, VEGF receptor (VEGFR)1, VEGFR2, and IGFBP2, than females. 47,48 In contrast, Rudnicki et al 49 showed that female adipose mice and human EC have higher proliferation and angiogenesis and less inflammation than male adipose EC females. In addition, using male and female human umbilical vein EC, Cattaneo et al 50 observed that male cells had higher apoptotic rates in response to serum starvation conditions and identified protein PTX3 (pentraxin-related protein 3) as a potential mediator of this apoptotic response and discovered that female EC expressed higher levels of eNOS (endothelial nitric oxide synthase).…”
Section: Discussionmentioning
confidence: 99%
“…46 Also, recent studies provided evidence that male rats and humans are more prone to corneal neovascularization than females and that males had a higher level of pro-atherogenic molecules, including VEGF (vascular endothelial growth factor)-A, VEGF receptor (VEGFR)1, VEGFR2, and IGFBP2, than females. 47,48 In contrast, Rudnicki et al 49 showed that female adipose mice and human EC have higher proliferation and angiogenesis and less inflammation than male adipose EC females. In addition, using male and female human umbilical vein EC, Cattaneo et al 50 observed that male cells had higher apoptotic rates in response to serum starvation conditions and identified protein PTX3 (pentraxin-related protein 3) as a potential mediator of this apoptotic response and discovered that female EC expressed higher levels of eNOS (endothelial nitric oxide synthase).…”
Section: Discussionmentioning
confidence: 99%
“…The effects were more pronounced in males than females, and NHMI administration increased the frequency of hyperplastic lesions with augmentation by chrysotile (although this was not statistically significant), but a 'promoting' effect of chrysotile was observed for the induction of lung tumors (all but two out of 11 primary tumors were in rats treated with both NHMI and chrysotile), although this finding was not confirmable statistically because of the small number of tumors observed. A sex difference in inflammatory responses involving higher expression of Cox-2, VEGF-A, and VEGF-R2 in males compared with females has recently been observed in other models [95], and consequently, research bodies now recommend use of sex-matched cohorts [96].…”
Section: The Synergy Between Asbestos Fibers and Tobacco Smoke For Lung Cancer Causation-animal Studiesmentioning
confidence: 99%
“…COX-2 is an inducible enzyme, which not only participates in various inflammatory reactions but also plays a role in the process of angiogenesis. Under various stimuli, its expression is slightly up-regulated (23)(24)(25). VEGF is closely related to the formation of new blood vessels.…”
Section: Corneal Cox-2 and Vegf Gene Mrna Level Detection Resultsmentioning
confidence: 99%